A two-step damage assessment method based on frequency spectrum change in a scaled wind turbine tripod with strain rosettes. (September 2018) - Soman, Rohan; Mieloszyk, Magdalena; Ostachowicz, Wieslaw
Abstract: The paper presents a proof of concept of a two-step methodology for the damage detection and localization in a scaled model of an offshore support structure. Two damage scenarios have been simulated for validating the methodology. The first damage scenario investigated is deterioration of the support condition which is simulated by removing the attachment of a leg of a tripod to the table and the second scenario is simulated by unbolting the flange to create an artificial circumferential crack in the upper brace of the tripod structure. The strain measurements have been obtained from a network of Fibre Bragg Grating (FBG) sensors bonded to the model. The damage detection is carried out in the first step using the root mean square deviation (RMSD) estimator. If the RMSD value is above a certain threshold, damage is said to be detected. Experimental results show that additional peaks appear in some frequency regions revealing vibration modes which are associated with damage in the structure. Applying the RMSD estimator to the regions where new peak has emerged it is possible to detect the damage. Once the damage is detected the damage isolation factor (DIF) is used for the damage isolation (level II damage detection). The DIF is based on the RMSD as well, and involves normalization using the rosette set values. Based on the results, it is seen that the DIF shows good localization performance. This good performance can be attributed to the ability of the parameter to overcome biases due to higher relative amplitude of vibration of some rosettes. Highlights: New two-step methodology for damage detection and isolation. A novel metric for damage isolation. Validation of methodology with experimental results on a scaled tripod model with hammer and wave excitation.